Exploring the mediating effects of amino acids on BMI and gestational diabetes mellitus: a longitudinal population-based cohort study - Wang, Lijuan; Wang, Haiyan; Gou, Xiaoyan; Li, Pengsheng; Fan, Dazhi; Huang, Fang; Yu, Dandan; Yang, Xingni; Suo, Dongmei; Liu, Zhengping; Chen, Gengdong; Zhou, Zixing (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the associations between pre-pregnancy BMI, amino acid metabolism in early pregnancy, and glucose levels/gestational diabetes mellitus (GDM) in later pregnancy. We also examined the mediating effects of amino acids on BMI and glucose.MethodsThe cohort study examined the association between BMI, first-trimester amino acids, and glucose/GDM among 1074 pregnant women. Regression analyses detected changes in amino acid levels and glucose measurements from oral glucose tolerance test (OGTT) at the 10th, 50th, and 90th percentiles. A mediation analysis was conducted to determine if amino acids mediated the relationship between BMI and glucose/GDM.ResultsFour essential amino acid concentrations (leucine, phenylalanine, threonine, and valine) increased significantly with increasing BMI (P < 0.05). Additionally, overweight women exhibited higher levels of non-essential amino acids (alanine, arginine, asparagine, aspartate, proline, tyrosine) and ornithine than underweight and normal-weight women. Women with GDM demonstrated higher levels of leucine, valine, alanine, asparagine, proline, and tyrosine compared to those without (P < 0.05). Fasting blood glucose (OGTT0) increased by 0.07 mmol/L when alanine levels increased by 50%. Similarly, increasing asparagine and leucine levels by 50% led to a 0.24 mmol/L increase in 1-hour postprandial blood glucose (OGTT1). A 50% rise in alanine, asparagine, and leucine levels led to average increases of 0.31, 0.19, and 0.21 mmol/L in mean 2-h postprandial blood glucose (OGTT2). These associations were statistically significant at the upper 90th percentile of the OGTT2 distribution. 50% increase in valine was correlated with a 0.22 mmol/L increase in mean OGTT2. The levels of alanine accounted for 11.76%, 8.08%, and 11.38% of the associations between BMI and GDM, OGTT0, and OGTT2, respectively. Additionally, the indirect effect of BMI-associated OGTT2 on leucine levels was estimated to be 5.39 percent.ConclusionAmino acid metabolism is correlated with BMI, GDM, and glucose levels. Notably, BMI and GDM/glucose intolerance are significantly mediated by alanine and leucine levels. This suggests a new way to study why overweight or obese mothers are more likely to develop GDM and glucose intolerance.